ESTIMATE THE BRITTLENESS INDEX OF DIGITAL ROCK IMAGE OF CARBONATE-CLASTIC - Christofel Josephus, David
As one of the countries with the largest consumption of fossil energy, it encourages an increase in oil production in Indonesia through the new field’s exploration or enhancement of the well productivity. Oil reservoirs are often found in carbonate rocks with good porosity but poor permeability. Hydraulic fracturing is one permeability enhancement technique that analyzes rock's brittleness index. Digital rock physics is a modern method to obtain elastic properties, an important parameter in brittleness index estimation by combining rock micro CT-Scan with the numerical method. This study focuses on analyzing the effect of variation in mineral content, fluid type and saturation, and porosity on the brittleness of rock. On the other hand, estimate the brittleness of DCJ28 carbonate with a sub-cubic variation. Calculations were performed using the DJROPS GUI Program which was developed from Garboczi’s elasticity calculations. The data used are 2 digital images of carbonate with a size of 501 x 482 x 450 pixels which are cropped into sub-cubes of 50 pixels3 and 1000 x 1000 x 750 pixels into 100 pixels3. Calculating stress and strain with a numerical approach to producing the modulus elastic, and then the brittleness index can be approximated. The result shows calcite, ankerite, and dolomite are minerals resistant to compression, shear, and tensile forces compared to quartz but quartz is not easily deformed as imaged by the Poisson’s ratio value. Increased fluid saturation decreases the modulus value linearly in the oil case and suddenly in the gas case. The greater the total porosity of the material or rock, the more elastic and easily deformed it is. The effect on brittleness increases when water is replaced by fluids (either oil or gas) but decreases when the content of calcite, ankerite, dolomite, and total porosity increase. The DCJ28 carbonate sample has a porosity of 24 %, on varies sub-cubic in the range of 3 – 65 %, and has 3 main minerals, calcite, ankerite, and quartz, with ankerite minerals being the largest mineral by segmentation and the cross correlation with XRD and thin slice data. Subcubic is obtained randomly or represents a certain maximum or minimum value which varies with porosity and mineral respectively. The DNTY-9 sub-cubic represents the largest porosity, the lowest volume of ankerite and quartz fractions is the sub-cubic with the lowest elastic modulus value and the largest Poisson’s ratio and resulting in the smallest brittleness index while the DNTY-10 sub-cubic the largest shear andiv Young modulus values and the smallest of Poisson’s ratio but has the largest brittleness index So this study concludes, is calcite, ankerite, and dolomite and increasing porosity make the material more ductile but more pores filled with fluid will make it a little more brittle. while the brittleness index of DCJ28 carbonate samples ranged from 12.3 – 535.9 where DNTY-9 was the most elastic sub-cubic and DNTY-10 is the most rigid or brittle sub-cubic